Intervención con soporte social y rehabilitación basada en la comunidad para personas con discapacidad, Santa Rosa, 2016. - Carrasco Luzarraga, Lyzzy Verónica (2017)
Despite multiple actions that have been made to improve the conditions of people with disabilities, it is still necessary the development of interventions with biopsychosocial approach. The interventions which decrease such dependence on people with disabilities are necessary to improve their functionality, and the practitioners of primary level are the optimal choice for the development of the same ones because of the close proximity to the community. The objective of this study was to evaluate the results of six months of intervention with focus on social support and the community-based rehabilitation strategy on the functional dependence of people with disabilities. A non-randomized, uncontrolled, and quasi-experimental study was carried out in which 30 people with physical disabilities participated. Some instruments have been used, such as: A socio-demographic questionnaire, The Barthel Index (BI) to evaluate the functional dependence, the Medical Outcomes Study - Social Support Survey (MOS) for measuring the social support, and the follow-up matrix of The Community-Based Rehabilitation Strategy (CBR) to evaluate its application. At the end of the intervention, the participants were re-evaluated using the same outcome measures. There was no loss of participants. The group taken for the study participated in workshops, lectures, training and physical exercise at the community level from the perspective of the strategy, these activities were implemented by human talent previously qualified. The Wilcoxon signed-rank test was taken for the BI (Z - 3.698, p < 0.05 = 2,177 x 10-4) as well as for the CBR strategy (Z - 4.714, p < 0.05 = 2.43 x 10-6), and relating to the MOS questionnaire, we used T Student for the sample related (t - 4.69, p < 0.05 = 5.85 x 10-5), significant differences were found before and after the measures applied. When applying the intervention with social support and the CBR strategy, it is concluded that there is a positive impact by improving the functional dependence on the involved population. Key words: Physical disability, social support, CBR, functional improvement, programs.